Recent Advances in Emerging Non‐Lithium Metal–Sulfur Batteries: A Review. Issue 24 (5th May 2021) - Ma, Lianbo; Lv, Yaohui; Wu, Junxiong; Chen, Yuming; Jin, Zhong
Abstract: Rechargeable non‐lithium metal–sulfur batteries (MSBs) have gained tremendous attention because of their merits, including a high theoretical capacity, remarkable energy density, and low cost. However, the detrimental issues encountered by non‐lithium MSBs, such as polysulfide shuttle effects, volume expansion and the low electrical conductivity of elemental sulfur, and the serious side reactions between metal anodes and electrolytes, severely restrict their practical applications. To circumvent these issues, numerous effective strategies have been explored and utilized. In this review, the intractable obstacles that prevent the application of non‐lithium MSBs are first summarized. Recent pioneering studies on rechargeable non‐lithium MSBs are reported and discussed in terms of material design, fabrication methods, and electrochemical performance. The emerging characterization techniques used to reveal the working mechanisms of non‐lithium MSBs and the advantages of elaborately designed structures are highlighted. Finally, the remaining issues and possible future areas of research for practical applications are discussed. Abstract : Non‐lithium metal–sulfur batteries (MSBs) have caught tremendous attention owing to their merits including high theoretical capacities, high energy densities, and low costs. This review systematically summarizes the recent progress in non‐lithium MSBs from the viewpoints of design concepts, fabrication methods, and electrochemical performance. This review provides new insights into the practical applications of non‐lithium MSBs.